In vivo Pharmacodynamic and Pharmacokinetic Interactions of Hibiscus sabdariffa Calyces Extracts with Simvastatin (2017)
What is known and objectives: Increasing number of patients use herbs with their medications. Such practice may result in beneficial or harmful herb-drug interactions. A recent survey reported that some participants co-administered Hibiscus sabdariffa, a widely used beverage, or tea, with their antihyperlipidaemic medications. This study therefore evaluated the effect of concomitant administration of Hibiscus sabdariffa calyces’ extracts with simvastatin on hyperlipidaemia and pharmacokinetics of the drug in vivo. Methods: Factorial experimental designs were used to evaluate the comparative effectiveness and interactions between simvastatin and aqueous extract of Hibiscus sabdariffa (AEHS) on lipid profile parameters in hyperlipidaemia-induced Wistar rats. Different combinations of low (AEHS 250 mg/kg; simvastatin 10 mg/kg) and high doses (AEHS 500 mg/kg; simvastatin 20 mg/kg) were administered individually and concurrently daily for 2 and 4 weeks. Lipid profile parameters were assessed at these treatment periods. Subsequently, the effect of aqueous beverage of Hibiscus sabdariffa (ABHS) on the pharmacokinetics of single-dose 40 mg simvastatin was also evaluated in six healthy human volunteers using two-period randomized crossover design. Blood samples were collected at predetermined times for 24 hours. The plasma obtained was analysed for simvastatin using RP-HPLC/ UV method. Results: Aqueous extract of Hibiscus sabdariffa reduced total cholesterol (Tc) better than simvastatin (P = .031). Low-dose AEHS and low-dose simvastatin used concomitantly caused 38.3% and 57.4% reductions in Tc and triglyceride levels, respectively, compared with low-dose simvastatin (P < .05). Also, ABHS increased clearance and reduced peak concentration of simvastatin by 44.6% and 18.0%, respectively (P < .05). The geometric mean ratio of simvastatin AUC0-∞ with or without ABHS was 0.646 with the 90% confidence interval (0.564, 0.758) falling outside the bioequivalent range. What is new and conclusion: Aqueous extract of Hibiscus sabdariffa lowered Tc better than simvastatin and enhanced the antihyperlipidaemic activity of the drug when co-administered at low doses in an animal model. However, aqueous beverage of Hibiscus sabdariffa caused a significant herb-drug interaction resulting in overall reduction in exposure to simvastatin in humans. Caution should thus be placed on clinical judgement or recommendations based on the animal results. Nevertheless, co-administration of the beverage with simvastatin should be discouraged until more clinical data are available.